Ontogenetic and short-term fluctuations in the residence depth of young pelagic stages of Munida gregaria in different zones of northern Patagonia. (May 2019) - Castro, Leonardo R.; Soto-Mendoza, Samuel; González-Saldías, Fernanda
Highlights: The mean weighted depth (centroids) of the early life stages occurred below the pycnocline. Both distance of centroid from pycnocline and vertical ranges differed among stages and sites. High late zoea and megalopa abundances agreed with the reported winter reproductive season. Increased abundances of late zoea and megalopa at flood tides suggest onshore transport. Abstract: In recent decades, the distribution of the very abundant squat lobster, Munida gregaria, a key species in the Beagle Channel and southernmost Patagonian waters, has widened towards lower latitudes. The general objective of this study was to assess how early life stages of this species cope with changes in environmental conditions at sites within its northern distribution in the Chilean Patagonia. In particular, we were interested in determining: (i) whether the various developmental stages of M. gregaria inhabited different mean depth ranges, (ii) whether diel vertical migrations were present in all stages and, (iii) if they occurred, whether these migrations were modified at sites with contrasting environmental conditions. The study consisted of high-frequency (every 3 h) observations over 30-h periods at each hydrographic and stratified sampling site of a springtime oceanographic cruise. Our results showed slight variations in preferences for hydrographic characteristics among stages, differences in their relative abundance in each sampling zone, and fluctuations in the mean weight by depth of distribution among sites. However, larval behavior showed certain similarities: the abundance and vertical distribution of most stages seemed to fluctuate with the semidiurnal tides, apparently not following the day-night cycle. For all stages, the weighted mean depth (centroids) was located below the pycnocline, although the mean distance from it and vertical displacement ranges differed among stages. Late zoea and megalopa were the most abundant stages, increasing in abundance at flood tides, in agreement with the previously reported winter reproductive season and the hypothesis of inshore-offshore ontogenetic movement of plankton stages for this species, which predicts that inshore transport should occur at this time of year. In summary, our results suggest that ontogenetic changes in vertical distribution and migrations and their respective deviations at each location constitute a flexible behavior that may facilitate dispersal towards new habitats and enhance the species' chances of survival under changing environmental conditions.